2003
DOI: 10.1016/s0028-3932(03)00122-2
|View full text |Cite
|
Sign up to set email alerts
|

The irrelevant speech effect: a PET study

Abstract: Positron emission tomography (PET) was performed in normal volunteers during a serial recall task under the influence of irrelevant speech comprising both single item repetition and multi-item sequences. An interaction approach was used to identify brain areas specifically related to the irrelevant speech effect. We interpreted activations as compensatory recruitment of complementary working memory processing, and decreased activity in terms of suppression of task relevant areas invoked by the irrelevant speec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
44
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 83 publications
4
44
1
Order By: Relevance
“…The elderly probably had difficulty suppressing task irrelevant input (such as scanner noise) (see also Amenedo andDiaz 1998, Meulenbroek et al, 2004). This idea is in line with studies investigating effects of attention on visual processing (Gisselgard et al, 2003, Petersson et al, 1999a,b, Rouleau and Belleville 1995, which showed that task-irrelevant processing can be suppressed by, for instance, deactivation of the auditory cortex. Hence, one might speculate that elderly participants have more difficulty focusing their attention on task-relevant visual input.…”
Section: Discussionsupporting
confidence: 80%
“…The elderly probably had difficulty suppressing task irrelevant input (such as scanner noise) (see also Amenedo andDiaz 1998, Meulenbroek et al, 2004). This idea is in line with studies investigating effects of attention on visual processing (Gisselgard et al, 2003, Petersson et al, 1999a,b, Rouleau and Belleville 1995, which showed that task-irrelevant processing can be suppressed by, for instance, deactivation of the auditory cortex. Hence, one might speculate that elderly participants have more difficulty focusing their attention on task-relevant visual input.…”
Section: Discussionsupporting
confidence: 80%
“…To address this question, positron emission tomography was used to identify brain regions activated by irrelevant speech at a relatively high working memory load. In the previous study (Gisselgård et al, 2003), the main finding was a bilateral relative deactivation in the superior temporal cortex corresponding to ISE. In this study, we wanted to investigate if this was present also at a higher load.…”
Section: Introductionmentioning
confidence: 80%
“…The functional anatomical correlate of this effect, based on the Baddeley -Hitch working memory model (Baddeley, 1992(Baddeley, , 2003, is thought to be localized to the verbal component of working memory (Baddeley, 2000;Larsen and Baddeley, 2003) associated with inferior frontal Burton, 2001;Jonides, 1997, 1999), superior temporal (Paulesu et al, 1993;Petersson et al, 2000;Price et al, 1999), and posterior parietal (Awh et al, 1995;Jonides et al, 1998a,b;Paulesu et al, 1993) areas of the brain. In a previous functional imaging study of ISE (Gisselgård et al, 2003), using a relatively low working memory load, the results indicated that the interference from irrelevant speech during immediate serial recall was associated with decreased regional blood flow in the mentioned cortical regions, in particular the superior temporal cortex. These findings were interpreted in terms of a suppression of phonological processing (Ghatan et al, 1998).…”
Section: Introductionmentioning
confidence: 83%
“…This effect might be related to a deficit in suppressing irrelevant input like scanner noise in old age. Several studies investigating the neural correlates of attentional modulation of visual processing tasks found that task-irrelevant processing needs to be suppressed by deactivation of, for instance, the auditory cortex (Ghatan et al, 1998;Gisselgård et al, 2003;Petersson et al, 1999b;Shulman et al, 1997). Also, the relatively stronger activation of the anterior cingulate cortex in old subjects as compared to young (Figs.…”
Section: Discussionmentioning
confidence: 96%